Time trends in ability level and functional outcome of stroke and multiple sclerosis patients undergoing comprehensive rehabilitation in Slovenia - Vidmar, Gaj (Zdravstveno varstvo, 2011)
Background: The University Rehabilitation Institute in Ljubljana provides comprehensive rehabilitation for the whole territory of Slovenia. The aim of the study was to verify a clinical observation that the demandingness of rehabilitation has been increasing because of a decrease in patients' functional abilitites on admission, with rehabilitation outcomes having remained unchanged or even improved. Methods: Functional Independence Measure (FIM) scores of 651 cerebrovascular insult (CVI) and 151 multiple sclerosis (MS) patients gathered between September 2004 and September 2006 (all eligible cases) were compared with those for patients with the same diagnosis (N=144 and 74, respectively) collected during the period from September 1999 to September 2000 (a random sample), considering only first-admission cases. The average FIM (motor, cognitive and total) scores and FIM gain after rehabilitation during the two periods were determined for each diagnostic group adjusted for patient age. Rehabilitation efficiency and effectiveness levels were compared in the same way. Effect Size and Standardised Response Mean were also analysed. Results: There were no differences in gender structure of the groups between the periods studied. During the recent period,the average age was higher by around two years in both groups. The length of stay was marginally shortened for CVI patients and remained unchanged for MS patients. There were no differences between the two periods concerning the time elapsed since stroke. In both groups, admission motor and cognitive FIM scores were on average approximately five points lower in the recent period, while the average rehabilitation gain from admission to discharge increased over time (in total by 1 in CVI patients and by 3 in MS patients). Regarding motor and total FIM scores, the standardised gain, rehabilitation efficiency and rehabilitation effectiveness increased as well. Conclusions: The Institute is admitting more severely affected patients than it did five to ten years ago, and parallelly the patient age has increased. Despite that and notwithstanding the tendency towards shorter rehabilitation, expected age-adjusted functional independence gain, rehabilitation efficiency, rehabilitation effectiveness, and the standardised functional independence gain have increased.
Keywords: možganska kap; multipla skleroza; Multiple Sclerosis; ocenjevanje izidov; Outcome and Process Assessment (Health Care); rehabilitacija; Rehabilitation Centers; Stroke; vocational rehabilitation